Unbreakable - Mehl, Nancy (Mehl, Nancy. Road to Kingdom, 2013)
"As her Mennonite town is shaken by strange incidents and outright attacks on its residents, Hope Kaufmann is forced to question all she knows and believes"--Provided by publisher.